Prognostic Value of Hepatorenal Function By Modified Model for End‐stage Liver Disease (MELD) Score in Patients Undergoing Tricuspid Annuloplasty - Yan Chen; Ying‐Xian Liu; Wai‐Kay Seto; Mei‐Zhen Wu; Yu‐Juan Yu; Yui‐Ming Lam; Wing‐Kuk Au; Daniel Chan; Ko‐Yung Sit; Lai‐Ming Ho; Hung‐Fat Tse; Kai‐Hang Yiu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background The Model for End‐stage Liver Disease excluding international normalized ratio (MELD‐XI) score and the modified MELD score with albumin replacing international normalized ratio (MELD‐Albumin) score, which reflect both liver and renal function, have been reported as predictors of adverse events in liver and heart disease. Nonetheless, their prognostic value in patients undergoing tricuspid annuloplasty has not been addressed. Methods and Results A total of 394 patients who underwent tricuspid annuloplasty were evaluated. Baseline clinical, laboratory, and echocardiographic parameters were recorded. Adverse outcome was defined as the occurrence of heart failure requiring admission or all‐cause mortality. Patients who underwent tricuspid annuloplasty had a high prevalence of preoperative hepatorenal dysfunction that was more common in patients with severe tricuspid regurgitation than those with mild to moderate tricuspid regurgitation. The MELD‐XI and MELD‐Albumin scores were excellent predictors of 1‐year adverse outcome (area under the curve: 0.69 and 0.75, respectively). Kaplan–Meier survival curve demonstrated that a high score on MELD‐XI (≥12.0) and MELD‐Albumin (≥10.7) was associated with an increased risk of adverse events. During a median follow‐up of 40 months, both MELD‐XI and MELD‐Albumin scores were significantly associated with adverse outcome, even after adjusting for potential confounding factors. Significant improvement of hepatorenal function at 1 year postoperation was noted only in patients who had no adverse events, not in those who experienced an adverse outcome. Conclusions Both MELD‐XI score and MELD‐Albumin score can provide useful information to predict adverse outcome in patients undergoing tricuspid annuloplasty. The present study supports monitoring of modified MELD score to improve preoperative risk stratification of these patients.